RANCANG BANGUN SISTEM INFORMASI REKAM MEDIS ELEKTRONIK BERBASIS WEBSITE DENGAN METODE WATERFALL - MUHAMMAD FARIZAL AKBAR; Sucipto; Dwi Harini (Department of System Information, 2026)
Abstract. The digital transformation of health services in Indonesia is mandated by Ministry of Health Regulation No. 24 of 2022, which requires all health facilities to implement Electronic Medical Records (EMR). PKU Muhammadiyah Kertosono Clinic still relies on manual, paper-based records and Microsoft Excel, leading to data duplication, inefficiency, and limited access to patient medical histories. This study aims to design and develop a web-based EMR Information System using the Waterfall method. The system was developed with PHP, CodeIgniter 4 framework, and MySQL database, covering five Waterfall stages: requirements analysis, system design, coding, testing, and maintenance. Black Box Testing of 25 functional scenarios — including patient registration, queue management, SOAP-based medical record input, digital prescriptions, pharmacy management, automated medical letters, and reporting — yielded a 100% success rate. The resulting system centralizes patient data management, eliminates manual record-keeping risks, and supports PKU Muhammadiyah Kertosono Clinic in complying with applicable health regulations.